Conservación de la tradición oral en el poblado de jatanca, distrito de san pedro de lloc, provincia de pacasmayo - la libertad - Cueva García, Sinthya Eveling (2016)
This research was conducted in order to identify the factors that lead to the gradual extinction of the oral tradition and the effects it has on social relations and cultural identity in Jatanca- District of San Pedro de Lloc, Province of Pacasmayo - La Libertad it is the central problem that seeks to respond to the likely factors affecting their gradual extinction. The proposed design was simple descriptive. The hypothesis proposed that television affects the education system and the lack of public policies are the factors causing dieback of the Oral Tradition as a form of social relationship and signal identity. In the case, the methodology was essentially qualitative (in-depth interview and discussion group), combined with the application of a survey (quantitative methodology), only for purposes of check specific details. Similarly, Comparative historical method, Ethnographic, inductive, deductive and Analytical Synthetics were used. We worked with a sample of 27 people. The results confirm our hypothesis and are oriented according to the research problem. Indeed, 74% of the population does not know the meaning of oral tradition, 81%, states that are narratives, with regard to poor practice of passing on traditions in the town, 44% is for work and 26 % under the influence of TV. At the same time, significant stories of oral tradition Jatanca as evidence of a particular cultural structure and wide identity influence were collected, which have facilitated the design of a technical proposal aimed at the conservation, protection and enhancement of the oral tradition to ensure its sustainability.